Effect at lumbar spine of workers when pushing rail cars loaded with fresh fruit bunches of oil palm - Laverde Albarracín, Cristian (2018)
According to the European Agency for Safety and Health at Work, work-related musculoskeletal disorders are changes in body structures such as: muscles, joints, tendons, ligaments, nerves, bones, and the circulatory system, fundamentally due to the effect of the work conditions and its environment. The objective of this study was to evaluate whether when pushing rail cars loaded with fresh fruit bunches in the sterilization area causes effect on workers’ lumbar spine. The study consisted of a descriptive study through direct observation, with the aid of the OWAS method and a specific medical examination to 45 workers. Several working positions when pushing the cars to the autoclaves were identified: General work position, spine position, arms position, and load or force exerted. The medical examination starting with the test of Lasegue reported positive for 22% of workers, whilst 78% reported negative; in the same way, reversed Lasegue maneuver; whereas Bragard’s sign showed 7% and 93% for positive and negative respectively. Therefore, the load exerted for the identified positions have significant negative effects on the musculoskeletal system at lumbar